Synthesis and biological evaluation of a water-soluble phosphate prodrug salt and structural analogues of KGP94, a lead inhibitor of cathepsin L. Issue 5 (1st March 2017) - Parker, Erica N.; Odutola, Samuel O.; Wang, Yifan; Strecker, Tracy E.; Mukherjee, Rajeswari; Shi, Zhe; Chaplin, David J.; Trawick, Mary Lynn; Pinney, Kevin G.
Graphical abstract: Abstract: The magnitude of expression of cathepsin L, often upregulated in the tumor microenvironment, correlates with the invasive and metastatic nature of certain tumors. Inhibition of cathepsin L represents an emerging strategy for the treatment of metastatic cancer. A potent, small-molecule inhibitor (referred to as KGP94) of cathepsin L, and new KGP94 analogues were synthesized. (3, 5-Dibromophenyl)-(3-hydroxyphenyl) ketone thiosemicarbazone (22 ), with an IC50 value of 202 nM, exhibited similar inhibitory activity against cathepsin L compared to KGP94 (IC50 = 189 nM). Due to limited aqueous solubility of KGP94, a water-soluble phosphate salt (KGP420) was prepared in order to facilitate future in vivo studies. Enzymatic hydrolysis with alkaline phosphatase (ALP) demonstrated that the phosphate prodrug, KGP420, was readily converted to the parent compound, KGP94.